THE MAIN DIRECTIONS OF INTERRELATION BETWEEN FINANCIAL SCIENCE AND FINANCIAL CULTURE - K. V. Ekimova; S. S. Galasova; V. V. Manuylenko (Вестник университета, 2020)
In order to identify the main directions of the relationship between financial science and financial culture, their formation of financial science and financial culture in retrospect and modern conditions has been considered. Induction, deduction, analysis, synthesis, historical method have been used in the study. According to the results of the study, it has been concluded, that financial science is a part of financial culture; together they perform the following functions: axiological (value), heuristic, educational, epistemological. The field of application of the results is financial science as a whole, its separate sections. The following areas of interaction between financial science and financial culture, the implementation of which will increase the level of financial science and culture, have been highlighted: education, informing the population about the protection of the rights of consumers of financial services, preparing citizens for life in old age.